A constituição do sujeito-administrador - Gomes, Eveline de Oliveira (2012)
The aim of this study was to analyze the constitution of the subject-administrator based on the conceptions of subject and discourse for Michel Foucault. Data collection was conducted through interviews, semi-structured type, with administrators working in two public universities in the state of Mato Grosso do Sul and were also gathered some documents relevant to the profession such as rules, regulations, political-pedagogical project plus some non-scientific publications in the area of Administration. Data were analyzed from elements of Foucauldian discourse analysis, especially those expressed in The Order of Discourse (2008) and The History of Sexuality 2 (2010b). We sought to show, from the discursive control, organizations that contribute to the constitution of the subject-administrator as the system CFA/CRAs and MEC. Regarding the ethical constitution, issues such as professional development, experience and professional practice and feel recognized as a holder of professional expertise were also evident throughout the analysis.